The Rights of Children as Perpetrators of Narcotics in the Legal System in Indonesia - Rizky Azhar Saragih (International Asia Of Law and Money Laundering, 2025)
Modern justice based on information technology has become an important issue since the Supreme Court of the Republic of Indonesia raised the issue of the digital age .The launch of the application was followed at a later stage, followed by the implementation of electronic hearings during the pandemic by District/ City Courts throughout Indonesia. The issue of digital-based modern justice continues to evolve on the issue of electronic courts.The term electronic court is an important study not only because of its philosophical basis and legality, but also very specific problems in the field of child protection, especially regarding the fulfillment of the rights of children who face the law during legal proceedings. This thesis aims to determine and describe the rights of children as perpetrators of narcotics crimes in the legal process in the children's rights Electronic Hearing during the pandemic by the court in the perspective of legislation based on cases that occur in the jurisdiction of the Lubuk Pakam District Court. The method used in this study is a qualitative approach to the type of case study research with a focus on cases of children dealing with the law in the District Court Lubuk Pakam 1A. The results of the thesis showed that the electronic court process provides a lot of convenience for children, but on the other hand many children's rights are neglected, including children who face the law because of narcotics crimes. In addition to the fulfillment of the right to assistance during the legal process, the waiver of the rights of the child also occurs in the child's recov.